Rattus norvegicus ... - Amr, Zuhair S.; Abu, Mohammad A.; Qumsiyeh, Mazin; Eid, Ehab (Zenodo, 2018)
Rattus norvegicus (Berkenhout, 1769) Common name: Norway rat or Brown rat. Diagnosis: Larger more robust rat, head body length about 380 mm, and tail 175 mm. The color is solid grayish brown above and below (Figure 76). Similar to R. rattus, but the tail is shorter than head and body length. Tail also with distinct epidermal scales. Six pairs of mammae. Large and very elongated skull, with parallel tempoparietal ridges. Tympanic bullae small and only little inflated. First upper molar without an anterolateral cusp (Figure 77). Localities: ‘ Ammān, Jarash, Irbid. Habitat: This species is associated with farm buildings in rural areas. Refuse tips, sewer systems, hedges and field margins are also suitable habitats for the brown rat. Biology: This is one the most prolific mammals. Females become sexually mature when they reach 8 to 12 weeksold. Gestation periodlasts for 21 and 23 days.It is possible to have 13 litters per year, each with seven to nine newborns.The Norway ratlive in groups, with a dominant male ... : Published as part of Amr, Zuhair S., Abu, Mohammad A., Qumsiyeh, Mazin & Eid, Ehab, 2018, Systematics, distribution and ecological analysis of rodents in Jordan, pp. 1-94 in Zootaxa 4397 (1) on pages 67-68, DOI: 10.11646/zootaxa.4397.1.1, http://zenodo.org/record/1202783 ...